Re-induction with L-DNR/FLAG Improves Response after AML Relapse, but not Long-term Survival - Creutzig, U.; Semmler, J.; Kaspers, G. L.; Reinhardt, D.; Zimmermann, M. (Klinische Pädiatrie, 2014)
Background: According to the results of the international study Relapsed AML 2001/01 response was better after re-induction with L-DNR/FLAG (liposomal daunorubicin, fludarabine, cytarabine, G-CSF) compared to FLAG only but survival rate was not improved. However, the findings might be group-specific.Method: Patient characteristics, actual therapy given and long-term course of the disease in 155 pediatric patients (including non-randomized) with first relapse and 10 primary nonresponders treated in Germany were analyzed.Results: Overall 4-year survival rates after relapse were similar in the 2 treatment groups L-DNR/FLAG and FLAG (0.43±0.05 vs. 0.47±0.06, p(log-rank)=0.47). The rate of randomization was low (65%) and 5% of the 101 randomized patients changed the treatment arm. Therefore, induction was based in 40% patients on an individual decision with preference for L-DNR/FLAG. There were less patients with favorable cytogenetics and morphology in the L-DNR/FLAG-group (p<0.04). Response to the first re-induction course at day 28 tended to be more unfavorable with FLAG only. In this patient group protocol intensifications were more frequent as compared to the L-DNR/FLAG-group (p=0.07), and late CR could be achieved after intensification in 9/18 poor responding patients.Conclusion: The initial selection bias of relapse patients with unfavorable risk factors to the disadvantage of the L-DNR/FLAG-group and the more drug- and time-intensive treatment after 1st re-induction given in the FLAG-group may have nullified the initial beneficial effect of L-DNR containing re-induction therapy and led to similar and relatively favorable survival rates in both treatment groups in Germany.
Keywords: AML relapse; children; re-induction therapy; liposomal daunorubicin; FLAG